2012
DOI: 10.1016/j.ijggc.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical modeling of changes in shallow groundwater chemistry observed during the MSU-ZERT CO2 injection experiment

Abstract: a b s t r a c tA field experiment involving the release of carbon dioxide (CO 2 ) into a shallow aquifer was conducted near Bozeman, Montana, during the summer of 2008, to investigate the potential groundwater quality impacts in the case of leakage of CO 2 from deep geological storage. As an essential part of the Montana State University Zero Emission Research and Technology (MSU-ZERT) field program, food-grade CO 2 was injected over a 30 day period into a horizontal perforated pipe a few feet below the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 49 publications
3
123
0
Order By: Relevance
“…It is also being used to interpret observed groundwater changes at CO 2 injection field experiments Yang et al, 2013a;Yang et al, 2014b;Zheng et al, 2012). For these studies, the most commonly applied models are TOUGHREACT (Xu et al, 2004) and PHREEQC (Parkhurst and Appelo, 1999).…”
Section: Geochemical Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also being used to interpret observed groundwater changes at CO 2 injection field experiments Yang et al, 2013a;Yang et al, 2014b;Zheng et al, 2012). For these studies, the most commonly applied models are TOUGHREACT (Xu et al, 2004) and PHREEQC (Parkhurst and Appelo, 1999).…”
Section: Geochemical Modellingmentioning
confidence: 99%
“…In other cases, complex mineralogical characterization of geological formations has been obtained from core analyses (e.g. XRD, SEM-EDS) (Keating et al, 2010;Keating et al, 2013b;Viswanathan et al, 2013;Zheng et al, 2012;Zheng et al, 2009). Such complex mineralogy allows one to predict impacts on water composition and the precipitation / dissolution of the main minerals (Humez et al, 2011;Zheng et al, 2012;Zheng et al, 2009).…”
Section: Geochemical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of their study was to understand the resulting pH changes and to evaluate the detectability of the acidic plume in the aquifer; the issue of mobilization of hazardous trace elements was not addressed. Zheng et al (2009) recently reported on a field experiment with CO 2 injection into a shallow aquifer in Montana. Preliminary groundwater analyses suggest that the dissolution of CO 2 leads to the mobilization of trace metals.…”
Section: Introduction and Approachmentioning
confidence: 99%
“…However, possible accidental leakage of CO 2 could degrade the water quality of overlying shallow aquifers [1][2][3][4][5]. Although numerous studies published in the literature have focused on the impact of pH decrease associated with CO 2 leakage on mobilization of naturally occurring hazardous trace metals and ions in aquifers due to processes involving desorption and dissolution [1,6,7], the effect of CO 2 leakage on bacteria and biofilms in shallow overlying aquifers has received very little attention [8][9][10].…”
Section: Introductionmentioning
confidence: 99%